Constructing the Local Wisdom Values of the Yel Lim Culture as a Historical Learning Source - Ufie, Agustinus; Ritiauw, Samuel P; Kubangun, Nur Aida (Paramita: Historical Studies Journal, 2020)
This study describes the living tradition of the indigenous people who live in a cluster of small islands in the southeast and south of the Maluku Islands, Indonesia, namely the Kei People. They have a robust local culture that influences in guiding and directing them to build social relations amid the onslaught of globalization with various attributes modernity that continues to go back and forth. The Yel Lim Culture, as the symbol and the identity of the Kei Community, radiates messages of humanity, tolerance, solidarity, and friendship, based on the life principle of siblings regardless of differences in ethnicity, religion, and race, it must continue to be preserved. To discover and then to elaborate on the main essence of the Yel Lim culture in the life of the Kei Community, a descriptive-analytical approach, as part of qualitative research, was taken. The results of this research showed that the Yel Lim Culture up to now was still being carried out because these cultural values were the guide, a guideline in realizing social order as a society that lived and developed in the Kei Islands. Observing the current social reality, then constructing Yel Lim's cultural values as a source in history class is very important in preparing future generations who have integrity and youthful identity, which is not easily trapped in various negative things because it continues to lean on local cultural values as their identity. Thus, the future generation that we build is the generation that is civilized and has virtuous and noble character as well. Ã‚Â Kajian ini mendeskripsikan tradisi masyarakat adat yang tinggal di kepulauan Kei Maluku Tenggara, dan memiliki budaya lokal dalam menuntun, mengarahkan mereka membangun relasi sosial walaupun ditengah-tengah gempuran arus modernisasi. Budaya Yel Lim sebagai simbol, identitas masyarakat Kei memancarkan pesan kemanusiaan, persaudaraan, toleransi, solidaritas dan silahturhami. Untuk menemukan, mempertahankan dan mengelaborasi budaya Yel Lim dalam kehidupan masyarakat Kei, sebagai salah satu sumber pembelajaran maka pendekatan deskriptif analitis sebagai bagian dari penelitian kualitatif ditempuh. Hasil penelitian ini memperlihatkan bahwa nilai-nilai budaya Yel Lim harus terus dimanifestasikan guna mewujudkan keteraturan sosial komunitas masyarakat adat Kei dari generasi ke generasi. Untuk itu, mengkonstruksi nilai-nilai budaya Yel Lim sebagai sumber pengembangan pembelajaran sejarah di Sekolah (SMP/SMA) sangatlah penting guna mempersiapkan generasi masa depan yang memiliki integritas, jati diri sehingga tidak muda terjerumus dalam berbagai hal negatif. Sehingga generasi masa depan yang kita bangun nantinya adalah generasi yang memiliki peradaban, budi pekerti luhur dan ahklak mulia. Ã‚Â